Diagnostic efficacy of digital hemoglobinometer (TrueHb), HemoCue and non invasive devices for screening patients for anemia in the field settings- a proposal - Neogi, Sutapa B; Negandhi, Himanshu; Sharma, Jyoti; Ray, Shomik; Saxena, Renu (Indian Journal of Community Health, 2018)
It is important to diagnose anemia at an early stage for appropriate and timely management. There is a need to have a device with good diagnostic accuracy, that is reliable and less expensive. Several methods are available for estimation of Hb. These have been reported to be piloted in small settings with encouraging results. However, for the purpose of screening at the national and state levels, we need a method that has high validity and is cost effective. Our study proposes to establish the diagnostic accuracy of some such devices that are available in India against automated analyzers (gold standard) for screening of anemia in laboratory and community settings.